STUDY OF COAL ASH AS COVER LAYERING TO PREVENT THE FORMATION OF ACID MINE DRAINAGE FROM COAL-FIRED POWER PLANT PT INDOMINCO MANDIRI - RAHMA RIZKITA (NIM : 12113004), NIKI
Mining activities are activities which removing overburden, regarding so sulfide minerals exposed so that it reacts with mineral water and air, which then formed The Acid Mine Drainage (AAT). AAT is characterized by high acidity or low pH values, thereby potentially pollute the environment. AAT must be managed, for example coat the rocks of acid-forming (Potential Acid Forming/ PAF) by using a material that is not potentially acid forming (Non Acid Forming/NAF) as a coating material that rock-forming acid does not react with air and / or water. However, the availability of materials NAF in the field is limited, alternative materials are required to meet the material needs of NAF. The mixture of coal ash to the overburden can be used as an alternative material to prevent the formation of acid mine water. Coal ash has alkaline properties that can neutralize acid-forming rocks. In addition, the size of the coal ash is relatively smooth, so it can easily fill the pores of coal ash - porous rock to prevent the diffusion of oxygen and water. However, coal ash contains metals - heavy metals that can pollute the environment. Therefore, it takes a physical and geochemical characterization of coal ash as a material mixing to prevent the formation of acid mine water. In this study, samples of coal ash was mixed with acid-forming rock samples to determine the ability of the coal ash to neutralize the acid. The parameters were reviewed as a result of this study are different types of coal ash comprising fly ash and bottom ash, coal ash mass composition used, and the grain size of the overburden.Based on research results, different types of ash and grain size did not show a difference value pH significantly. However, based on differences in the composition of the coal ash used mass showed a significant difference. , On the composition of fly ash at most have an average pH value of 7,86, while the composition of the fly ash has at least the average pH value of 6,07. On the composition of bottom ash at most have an average pH value of 7,73, whereas at least the composition of bottom ash has an average pH value of 4,51 Thus, coal ash can be used as material mixing to prevent the formation of AAT.